Dynamic mode decomposition analysis of plasma aeroelastic control of airfoils in cascade. (April 2020) - Neumann, P.; de Almeida, V.B.C.; Motta, V.; Malzacher, L.; Peitsch, D.; Quaranta, G.
Abstract: A dynamic mode decomposition (DMD) is carried out for the flow field in a compressor cascade with plasma actuators employed for aeroelastic control. Numerical assessments performed in previous works have shown that alternate triggering of pressure side/suction side actuators installed at the trailing edge of the blades can effectively reduce vibratory loads and enlarge the flutter boundaries of a linear compressor cascade. With the twofold aim of obtaining an in-depth understanding of the flow physics associated to plasma actuation and ultimately developing an optimized control law for the actuators, the dominant structures of the pressure field are extracted via a dynamic mode decomposition. The decomposition is conducted on the actuated and non-actuated pressure fields at several inter blade phase angles. The fundamental effects of plasma actuations on the flow field, and in turn on the blade loading, are identified and discussed. The procedure allows obtaining an useful picture of the main fluid mechanic phenomena associated to plasma aeroelastic control on turbomachinery blades. Additionally, the DMD spectrum and its coherence are analysed, yielding a wider energetic spread over high-order modes for the plasma-actuated case, in comparison to the clean cascade.